Pemodelan sistem dinamik untuk kota berketahanan iklim berpotensi bencana di Kota Malang - Angraini, Sinta (Maliki Interdisciplinary Journal, 2023)
This article discusses system dynamic modeling to develop a climate resilient city with the potential for disasters in Malang City. Climate change has become a pressing global issue, and cities like Malang City are facing an increased risk of natural disasters as a result. The system dynamic modeling approach is used as a tool to understand the complexity of city systems and identify factors that contribute to potential disasters. In this article, the author explains the context of climate change in Malang City and analyzes historical data about natural disasters that have occurred and that may occur in the future. System dynamic modeling is used to describe important components in cities, such as drainage systems, river flow patterns, and changes in land use. Climate resilience assessment is carried out by designing relevant indicators and parameters to measure the level of city climate resilience. Through modeling results, the authors